Risk Factors of Post-Tonsillectomy Bleeding and Differences Between Children and Adults: Implications for Risk Assessment - Bülent Öcal; Mehmet Murat Günay; Kemal Keseroğlu; Murad Mutlu; İlker Akyıldız; Cem Saka; Emel Çadallı Tatar; Mehmet Hakan Korkmaz (Turkish Archives of Otorhinolaryngology)
Objective: To investigate the association between clinical factors and post-tonsillectomy hemorrhage (PTH) including rebleeding episodes. Methods: The medical records of 1,082 patients who underwent tonsillectomy between May 2018 and April 2019 were reviewed. The entire study cohort included 431 (39.7%) children aged less than six years and 292 (26.9%) adults older than 15 years. Data on patient demographics, surgical indication, dissection technique, tonsils’ grade, postoperative analgesia, surgeon’s experience, the season of surgery, management of hemorrhage, length of hospital stay, and rebleeding episode were noted. Results: Postoperative hemorrhage occurred in 87 cases (8.0%) including 32 children (4.0% of children) and 55 adults (18.8% of adults). Age, surgical indication, tonsils’ grade, and postoperative use of non-steroidal anti-inflammatory drugs (NSAIDs) were risk factors found to be statistically significant for PTH in univariate analysis (p<0.05). Multivariable analyses identified patients older than 15 years and those who received postoperative NSAIDs to be risk factors of PTH [Odds ratio (OR): 15.5, 95% confidence interval (CI): 7.68-31.27, p<0.001, OR: 0.22, 95% CI: 0.11-0.44, p<0.001, respectively]. About one out of every 60 (1.5%) children had severe oropharyngeal bleeding, whereas every 12th (8.2%) patient of those aged >15 years had severe hemorrhages that warranted surgical hemostasis in the operating room (p<0.001). Conclusion: The risk of bleeding after tonsillectomy was significantly higher in adults and users of NSAIDs postoperatively. Also, the evidence of minor bleeding increased the risk of a second bleeding episode in adulthood.